Congenital bronchoesophageal fistula in an adult: a case report and radiologic review - Kim, Bo Sung; Kang, Eun-Ju; Lee, Ki-Nam; Choi, Pil Jo (Kosin Medical Journal (Online), 2018)
Congenital bronchoesophageal fistula (BEF) is rarely reported in adults in the English literature. Herein, we present a rare case of congenital BEF in a 43-year-old man that was incidentally found on esophagogastroduodenoscopy. Chest CT and barium esophagography revealed a fistula between his lower esophagus and the right lower lobe segmental bronchus. After the fistula was surgically treated, the fistula was no longer noted on follow-up barium esophagography.